Manufacturing processes, additional nutritional value and versatile food applications of fresh microalgae Spirulina - Luo, Guanghong; Liu, Haiyan; Yang, Shenghui; Sun, Zhongliang; Sun, Liqin; Wang, Lijuan (Frontiers in Nutrition, 2024)
Spirulina is capable of using light energy and fixing carbon dioxide to synthesize a spectrum of organic substances, including proteins, polysaccharides, and unsaturated fatty acids, making it one of the most coveted food resources for humanity. Conventionally, Spirulina products are formulated into algal powder tablets or capsules. However, the processing and preparation of these products, involving screw pump feeding, extrusion, high-speed automation, and high-temperature dewatering, often result in the rupture of cell filaments, cell fragmentation, and the unfortunate loss of vital nutrients. In contrast, fresh Spirulina, cultivated within a closed photobioreactor and transformed into an edible delight through harvesting, washing, filtering, and sterilizing, presents a refreshing taste and odor. It is gradually earning acceptance as a novel health food among the general public. This review delves into the manufacturing processes of fresh Spirulina, analyzes its nutritional advantages over conventional algal powder, and ultimately prospects the avenues for fresh Spirulina's application in modern food processing. The aim is to provide valuable references for the research and development of new microalgal products and to propel the food applications of microalgae forward.